THE CLASH OF INTERESTS BETWEEN CHINA AND RUSSIA IN THE GEOPOLITICAL BALANCE OF CENTRAL ASIA - Xudoyberdiyev Otabek Zafar o'g'li (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article explores the evolving geopolitical dynamics of Central Asia, focusing on the strategic competition and overlapping interests of China and Russia in the region. While Russia has maintained historical, cultural, and security-based influence over Central Asia since the Soviet era, China has rapidly expanded its presence through economic initiatives such as the Belt and Road Initiative (BRI). The paper examines how these two powers interact, collaborate, and compete within spheres such as infrastructure development, energy resources, security alliances, and political influence. It also analyzes the strategies of Central Asian states in balancing the interests of both powers to preserve their sovereignty and maximize national benefits.